Assessment of the efficacy of Chinese herbal medicine combined with western medicine for treating severe acute pancreatitis-related acute lung injury/acute respiratory distress syndrome: a systematic review and meta-analysis based on randomized controlled trials - Han, Xin; Zhang, Ming; Dou, Congcong; Shan, Lianfeng; Ni, Qingqiang (Frontiers in Pharmacology, 2025)
PurposeThis systematic review and meta-analysis aimed to evaluate the efficacy of Chinese herbal medicine (CHM) combined with Western medicine (WM) for treating severe acute pancreatitis-related acute lung injury/acute respiratory distress syndrome (SAP-ALI/ARDS).MethodsA comprehensive search of 12 English and Chinese databases yielded 13 randomized controlled trials (RCTs) involving 917 patients. The experimental group received CHM compounds combined with standard WM, while the control group received only WM. Outcomes included clinical efficacy, inflammatory markers (e.g., TNF-α, IL-6), disease progression indicators (e.g., time to abdominal pain relief, ICU stay), and mortality rates. The Cochrane Risk of Bias Tool was used to assess study quality, and meta-analysis was conducted using RevMan 5.4.ResultsThe meta-analysis demonstrated that CHM combined with WM significantly improved clinical efficacy (RR = 1.26, 95% CI: 1.17–1.37, P < 0.00001), reduced inflammatory markers (e.g., TNF-α: MD = −18.18 pg/mL, P < 0.00001; IL-6: MD = −24.70 pg/mL, P < 0.00001), and shortened disease progression indicators (e.g., time to abdominal pain relief: MD = −1.56 days, P < 0.00001; ICU stay: MD = −3.27 days, P < 0.00001). However, no significant difference in mortality rates was observed (RR = 0.47, P = 0.96).ConclusionThis study provides robust evidence that the combination of Chinese herbal medicine with Western medicine significantly enhances clinical outcomes for patients with SAP-ALI/ARDS. The findings highlight improvements in inflammatory markers, disease progression indicators, and oxygenation indices. However, the lack of significant differences in mortality rates and the limited methodological rigor of included studies (e.g., blinding and allocation concealment) are notable limitations. Future research should focus on optimizing RCT designs, exploring molecular mechanisms, and investigating long-term outcomes to strengthen the evidence base for integrated therapies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifer CRD42024579735.